SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) UNTUK MENINGKATKAN BIOAVAILABILITAS ROSUVASTATIN SEBAGAI UPAYA PENGOBATAN PADA PENYAKIT HIPERLIPIDEMIA - Akemah, Tracey Odella Jiraldi; Putri, Natasya Pramatya; Buanasari, Ni Nyoman Tri Eka; Indrayani, Agung Wiwiek (Essence of Scientific Medical Journal; Vol 21 No 1 (2023): Volume 21 No. 1 (Januari - Juni 2023) Essential: Essence of Scientific Medical Journal, 2023)
ABSTRACT Introduction: Hyperlipidemia is a disease with a high prevalence throughout the world. This disease is a condition where the cholesterol level or low-density lipoprotein cholesterol (LDL-C) in the blood is above normal levels. Rosuvastatin is classified as a statin drug with the highest effectivity to decrease the LDL-C levels so that hyperlipidemia can be treated well. The administration of rosuvastatin in small doses has the ability to reduce LDL-C levels better than other statin drugs that requires larger doses. The use of rosuvastatin orally is not maximal in the treatment of hyperlipidemia because the bioavailability of rosuvastatin is very low at around 20%. Therefore, a drug delivery system is needed to enhance rosuvastatin absorption. Discussion: SNEDDS is a newly modified drug classified as a lipid based drug delivery system (LBDDS) in the form of isotropic mixture consisting of oil, surfactants, and cosolvents or cosurfactants components. SNEDDS can increase drug solubility in the gastrointestinal tract by forming very small particles around <200 nm through nanoemulsions and increase the surface area between water and oil phases. Rosuvastatin in the form of SNEDDS can enhance its drug solubility and bioavailability by improving the pharmacokinetic profile of the drug. Conclusion: Rosuvastatin in the form of SNEDDS deserves further review because of its effectivity in causing significant changes to rosuvastatin’s low bioavailability, which is from 20% bioavailability enhanced to >80% through SNEDDS. Keywords: Bioavailability, hyperlipidemia, rosuvastatin, SNEDDS